Modelling charge transport in perovskite solar cells: Potential-based and limiting ion depletion. (10th September 2021) - Abdel, Dilara; Vágner, Petr; Fuhrmann, Jürgen; Farrell, Patricio
Abstract: From Maxwell-Stefan diffusion and general electrostatics, we derive a drift-diffusion model for charge transport in perovskite solar cells (PSCs) where any ion in the perovskite layer may flexibly be chosen to be mobile or immobile. Unlike other models in the literature, our model is based on quasi Fermi potentials instead of densities. This allows to easily include nonlinear diffusion (based on Fermi-Dirac, Gauss-Fermi or Blakemore statistics for example) as well as limit the ion depletion (via the Fermi-Dirac integral of order − 1 ). The latter will be motivated by a grand-canonical formalism of ideal lattice gas. Furthermore, our model allows to use different statistics for different species. We discuss the thermodynamic equilibrium, electroneutrality as well as generation/recombination. Finally, we present numerical finite volume simulations to underline the importance of limiting ion depletion.